Numerical investigation on the hydrodynamic behavior of a floating breakwater with moon pool through a coupling SPH model - Cui, Jie; Chen, Xin; Sun, Peng-Nan; Li, Ming-Yuan (Ocean engineering, 2022)
The moon pool opened in a floating structure significantly affects its wave attenuating performance. In this paper, the hydrodynamic behaviors of several floating breakwaters with moon pool were investigated preliminarily by the Smoothed Particle Hydrodynamics (SPH) method. For a comparative study, wave interactions with a rectangular floating breakwater and a cylindrical dual pontoon floating breakwater were also simulated. The wave was generated with a relaxation zone method which had displayed its accuracy as well as applicability. In addition, the lumped mass method was adopted to provide mooring forces for the floating breakwater. The coupling SPH model was validated by a physical model test and the numerical results were in good agreement with the experimental data. After that, the wave coefficients, such as transmitted wave coefficient, reflected wave coefficient and dissipated wave coefficient, were computed to evaluate the wave attenuating performance of floating body models. Meanwhile, for each model, the motion responses, including sway, heave and pitch, were analyzed to investigate their hydrodynamic performance. The numerical results and analysis are useful for the design of floating breakwaters, and the conclusions could be further applied in the design of wave energy converters. •A coupling SPH model is utilized to investigate the hydrodynamic behavior of floating breakwaters with moon pool.•A relaxation zone technique is adopted for wave generation in an SPH wave flume.•SPH results show good agreement with experimental data for the floating breakwater with mooring lines.•The shapes of the floating breakwater and its moon pool are shown to be important.